A Cross-Sectional Study of Physical Activity and Academic Performance Among Degree College Students in Davanagere - Anupama K; Rathnaprabha G K; Swathi H J (RGUHS National Journal of Public Health)
Background Physical activity is a key health indicator. Due to limited data from Davanagere it is important to study the physical activityrsquos impact on academic performance to address sedentary lifestyles and improve student performance. This study aimed to assess the prevalence and patterns of physical activity among degree college students in Davanagere and to evaluate the association between physical activity and their academic performance.Methodology A cross-sectional study was conducted among college degree students using a convenience sampling technique. A total of 400 students aged 18-22 years were interviewed using the official English long version of the International Physical Activity Questionnaire IPAQ. The total level of physical activity PA and activity in each of the four life domains ndash work transport domestic and gardening and leisure-time were estimated and were expressed as metabolic equivalent-hours per week MET-hourweek. Based on MET scores physical activity was categorized into low moderate or high. High PA was defined as gt3000 MET-hourweek moderate as 600-3000 MET-hourweek and those who did not meet these criteria were classified as low PA. Previous examination scores were used to assess academic performance.Results Among 400 students 210 students 52.7 involved in moderate physical activity while 170 students involved in low 42.5 and 20 students 5 involved in high physical activity. Physical activity was not found to be associated with academic performance P 0.77 age socioeconomic status or the degree program students were enrolled in. Females were found to be significantly engaged in physical activity P0.031.Conclusion Physical activity was found to be prevalent among degree college students highlighting its role as a positive health indicator.